Pengaruh Pemberian Massage dan Cooling Down terhadap Penurun Tingkat Kelelahan pada Atlet Olahraga Sepak Bola - Marliana Marliana; R. Sri Ayu Indrapuri (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to evaluate the effect of massage and cooling down on the reduction of fatigue levels in soccer athletes at the Angkasa Surakarta Soccer School. Physical fatigue experienced by athletes is often caused by high intensity and duration of training, as well as the accumulation of lactic acid in the muscles. The method used in this research is a quasi-experimental design with a pre and post-test approach on two groups. A total of 24 athletes were divided into two groups, where one group received massage intervention and the other group underwent cooling down sessions. The results of the analysis using the Wilcoxon test showed a significant effect of massage on reducing fatigue levels (p < 0.05), while cooling down did not show a significant effect. These findings indicate that massage is more effective in aiding muscle recovery from fatigue compared to cooling down. This study is expected to provide insights for coaches and healthcare practitioners in designing more effective recovery programs for soccer athletes.